Fish primary embryonic pluripotent cells assemble into retinal tissue mirroring in vivo early eye development - in vivo imaging of OV formation - Zilova, Lucie; Weinhardt, Venera; Tavhelidse-Suck, Tinatini; Schlagheck, Christina; Thumberger, Thomas; Wittbrodt, Joachim (Universität, 2021)
Development of a functional retina is accompanied by several morphological events transitions that ultimately result in the formation of a function...